2019
DOI: 10.34097/jeicom_1_1_1
|View full text |Cite
|
Sign up to set email alerts
|

Innovating in University Teaching Through Classroom Interaction

Abstract: Previous research has shown that the best educational practices are built on the basis of interaction in the classrooms, regardless of their level. However, the dialogue among the students themselves and between them and the teacher is still more scarce than desirable, especially in the university context. Taking this weakness into account, the authors of this contribution propose a Teaching Innovation Project (TIP) as a means of confronting the reality of this matter and advancing in it through an interdiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
2
Order By: Relevance
“…The testimonies collected show a high satisfaction of the people who approach these technologies and their great potential to promote interaction in teaching, especially in the asynchronous one, which is the most inaccessible, since it is developed in different times and spaces for professors and students (Alarcia & Bravo, 2012;Alvarez-Alvarez et al, 2019;Alvarez-Alvarez, 2017;Burns et al, 2020;Comer & Lenaghan, 2013;Hernández & Álvarez-Álvarez, 2018;Vercellotti, 2018). The testimonies collected also reveal an idea pointed out in the state of the art: the preference for graphic and visual material that helps to understand the contents (Arnone & Grabowski, 1992;Roberts, 2019;Silverajah & Govindaraj, 2018).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The testimonies collected show a high satisfaction of the people who approach these technologies and their great potential to promote interaction in teaching, especially in the asynchronous one, which is the most inaccessible, since it is developed in different times and spaces for professors and students (Alarcia & Bravo, 2012;Alvarez-Alvarez et al, 2019;Alvarez-Alvarez, 2017;Burns et al, 2020;Comer & Lenaghan, 2013;Hernández & Álvarez-Álvarez, 2018;Vercellotti, 2018). The testimonies collected also reveal an idea pointed out in the state of the art: the preference for graphic and visual material that helps to understand the contents (Arnone & Grabowski, 1992;Roberts, 2019;Silverajah & Govindaraj, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Previous research has shown that it is important to promote interaction in university teaching because it allows to promote teaching relationships based on dialogue, promote participation and encourage the involvement of students, as well as promote more effective teaching-learning processes (Alarcia & Bravo, 2012;Alvarez-Alvarez et al, 2019;Álvarez Álvarez, 2017;Burns et al, 2020;Comer & Lenaghan, 2013;Hernández & Álvarez-Álvarez, 2018;Vercellotti, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dada su relevancia para la mejora de la calidad de la enseñanza universitaria, el estudio de la interacción en los procesos de enseñanza-aprendizaje dentro del aula es un fenómeno con una larga trayectoria de investigación (Álvarez-Álvarez et al, 2019;Bai y Chang, 2016;Carr, 2015;Dwyer, 2015;Hardman, 2015;Steen-Utheima y Wittekb, 2017;Vercellotti, 2018;Wells, 2001). Autores como Vercellotti (2018) y Hardman (2015) muestran que la comunicación entre el docente y estudiantes, así como entre los propios estudiantes, es esencial para fomentar la interacción en el aula universitaria.…”
Section: Introductionunclassified
“…Aunque se han publicado varios trabajos sobre este tema (Álvarez-Álvarez et al, 2019;Exley, 2013;Duschl y Osborne, 2002;Gauci, Dantas, Williams y Kemm, 2009;Haneda, Teemant y Sherman, 2016;Majlesi y Broth, 2012;Scott, Montimer y Aguilar, 2006;Stockero, Rupnow y Pascoe, 2017), se ha detectado que no existe una definición comúnmente aceptada para el concepto "interacción". En este trabajo se toma como referencia la definición propuesta por Howe y Abedin (2013).…”
Section: Introductionunclassified